Social Inclusion : What Does It Mean for Health Policy and Practice? - Das, Maitreyi Bordia; Evans, Timothy Grant; Palu, Toomas; Wilson, David (World Bank, Washington, DC, 2017)
This paper applies the tenets of social inclusion to health policy and practice, arguing that achieving the goal of Universal Health Coverage (UHC) will be impossible without considering social and economic inclusion. The idea of social inclusion in the achievement of UHC goes well beyond a focus on local level interventions to an expansive notion that addresses the policy environment, social practices, and institutions. The paper summarizes ways in which social exclusion affects access to health services and health outcomes. It argues that social exclusion plays out through practices, processes, and behaviors of service providers, elites, and those most likely to be excluded. Such practices may permeate the structure and function of both formal and informal institutions. Through a discussion of the design and delivery of policies and programs, the paper highlights ways in which social inclusion can be advanced toward UHC. Finally, it draws from the experience of World Bank–supported interventions to highlight illustrative actions toward social inclusion in ways that can affect health outcomes. The expected audience of this paper are teams involved in the financing, design, and delivery of health programs, both within the World Bank and outside. The paper concludes with the exhortation to define the scope of “social inclusion” so that interventions can be targeted to those who are most likely to be excluded that interventions can be targeted to those who are most likely to be excluded.